Pendekatan Pengkajian Agama: Dalam Ruang Lingkup Antropologis - Arfadillah Hasri; Derlicia Utami; Maftuh Ajmain (PT. Hasba Edukasi Mandiri, 2026)
This study aims to understand the basic concepts of the anthropological approach in the study of religion, analyze its history and development in religious studies, and examine its relevance in the context of Islamic studies in Indonesia. The method used is library research with a descriptive-analytical approach to literature related to the anthropology of religion. The results show that the anthropological approach understands religious phenomena as an integral part of human culture, not merely as a system of doctrine, but as a living and meaningful cultural expression within a community's real life. The development of this approach has passed through several phases: evolutionism and comparativism (19th century), structural-functionalism (early 20th century), interpretive-symbolic (mid-20th century), to the contemporary phase integrating post-colonial, gender, and globalism perspectives. The main methods used include participant observation, ethnography, symbolic analysis, in-depth interviews, and genealogical and historical analysis. The anthropological approach has high relevance in Islamic studies in Indonesia because it is able to reveal the diversity of Islamic expressions that cannot be understood through a normative-theological approach alone.